How Much Space Does My Shade Tree Need? Planting Space Recommendations for Medium and Large Trees in Florida Cities - Deborah R. Hilbert; Andrew Koeser; Brooke L. Moffis; JuWanda G. Rowell; Drew C. McLean (EDIS)
Trees provide urban landscapes with shade, beauty, and habitat. They can also help lessen the effects of flooding and urban heat buildup while storing carbon dioxide, a major greenhouse gas. When planted in the wrong place, however, trees can damage urban infrastructure. To maximize the benefits provided by urban trees, we need better-informed tree selection and larger planting spaces with the capacity to support big-canopy trees. This new 8-page fact sheet is intended to help arborists, urban foresters, landscape designers, landscapers, and anyone else responsible for the planting of trees in developed areas make informed decisions regarding the planting width requirements of the trees they select. Written by Deborah R. Hilbert, Andrew K. Koeser, Brooke L. Moffis, JuWanda G. Rowell, and Drew C. McLean, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep592